The role of ionic liquid [C4C1im]Br as an adjuvant on the two‐phase formation and the extraction of l‐phenylalanine in ABS composed of PEG400 and potassium citrate at different temperatures. (6th August 2018) - Hamzehzadeh, Sholeh; Touri, Samira
Abstract : The potential of polyethylene glycol 400 + potassium citrate aqueous biphasic system (ABS) with ionic liquid (IL) 1‐butyl‐3‐methylimidazolium bromide ([C4 C1 im]Br) as an adjuvant is examined for the extraction ofl ‐phenylalanine (Phe), as a model biomolecule, at different temperatures and system compositions. The binodal curves and liquid–liquid equilibrium data were determined by the addition of 5 wt% IL to investigate its effect on phase diagrams and Phe partition coefficients. The results indicate that binodal curves of systems with and without IL are more deviated from each other with decreasing temperature. Moreover, IL has a high tendency to partition into the PEG‐rich phase. This tendency increases with increasing temperature and system compositions. For Phe, the partition coefficients obtained in this work (KPhe ≈ 5.5–81.2) are significantly higher than those observed in other conventional PEG‐inorganic salt ABS (KPhe ≈ 0.5–2.5), water‐immiscible ILs two‐phase extraction systems (KPhe ≈ 0.02–1.2), or even, in the IL‐based ABS with the same IL as the main phase‐forming component (KPhe ≈ 3.2). The phase hydrophobicity, salting‐out and π⋯π stacking seem to be the main driving forces to affect the extraction aptitude of the studied ABS for Phe. Furthermore, the performance of using [C4 C1 im]Br as adjuvant to improve the partition of Phe in the studied ABS at different temperatures seems to be ruled by the differences in the phases hydrophobicities. Finally, the experimental tie lines and partition coefficients are accurately correlated using the NRTL model. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1149–1166, 2018